Rapid Assesment Pencatatan Sipil dan Statistik Hayati di Tiga Daerah di Indonesia - Lukman Prayitno; Anwar Dede Musadad (Media Kesehatan Masyarakat Indonesia, 2020)
A good Civil Registration and Biological Statistics system are the basis for planning, monitoring, and evaluating development programs. Decision-makers and policies are highly dependent on timely, complete statistical data and reliable methods. Therefore it is necessary to do a Rapid Assessment which aims to conduct a quick evaluation of the strengths and weaknesses of the current birth, death, and cause of death registration system. The method is qualitative research with discussion methods and information confirmation. The rapid assessment questionnaire is from WHO. It contains 25 questions. The research location was chosen purposively, namely Padang Pariaman Regency, Makassar City, Kudus Regency. The research took place in August 2019. The total rapid assessment scores of Padang Pariaman Regency, Makassar City, and Kudus Regency were 42.67%, 49.33%, 57.33% respectively. The total scores in the 3 study areas are in the same range of values, 34-64%. This range of values ​​indicates that many aspects of the system are not functioning properly, and many problems require attention. Three research areas have different shortcomings. We need different strategies that depend on their characteristics and require cross-sector collaboration.